Análise do fundo de desenvolvimento industrial do Ceará – programa de incentivo ao desenvolvimento industrial sob a perspectiva da igualdade tributária e da proporcionalidade - Queiroz, Tiago Vasconcelos (2020)
This work’s aim is to discuss ICMS tax incentives granted through the Ceará Industrial Development Fund (FDI) – Incentive to Industrial Development Program (PROVIN) and to analyze them under the scope of equality and proportionality. The initial argument proposed is that equality is a human invention and is developed from a moral duty. Besides that, inequality is problematic to society as a whole, because it restrains economic growth, causes political instability and contributes to generate even more inequality. Due to the moral duty and the difficulties it causes, inequality must be fought by the government. That´s what the Brazilian Constitution mandates. With that in mind and considering that taxes have the capacity to influence and modify behaviour, the promotion of equality is made more effectively when tax incentives are used. Moreover, this obligation also falls on the shoulders of the federated states and not only the Union. Nevertheless, tax incentives granted by the federated states are heavily criticized because they promote harmful tax competition, they distort the price of goods in the economy, because it is difficult to verify their effectiveness, and lastly due the legal insecurity originated from some of the methods used to grant the incentives. Starting from data collection, inductive and deductive reasoning methods were used to construct the arguments and develop the theory that supports the conclusion. As a result, after analyzing the questions above presented, the work concludes that the FDI – PROVIN complies with the Brazilian Social State principles, that it respects equity of taxation and that it is a proportional measure, in its three aspects, being adequate, necessary and proportional in strict sense.